TINJAUAN RUPA DASAR SAMPUL BUKU “BIJAK BERBAHASA INDONESIA TEORI DAN APLIKASI” - Lejar Daniartana Hukubun (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2023)
Basic art is a science that is used to train the basics of art and design. All the needs of art, regardless of whether it is in the form of painting, interior design, dance, design, etc., must have something to do with this knowledge. This journal attempts to discuss the cover of the book